2022
DOI: 10.1021/acs.orglett.2c02331
|View full text |Cite
|
Sign up to set email alerts
|

Three-Component One-Pot Construction of 2-Aryl-4H-benzo[4,5]thiazolo[3,2-a]pyrimidines Using Solid Calcium Carbide as a Surrogate of Gaseous Acetylene

Abstract: A concise method for the construction of 2-aryl-4H-benzo[4,5]thiazolo[3,2-a]pyrimidines using solid calcium carbide instead of gaseous acetylene as an alkyne source and 2-aminobenzothiazoles and aromatic aldehydes as substrates through one-pot three-component cascade reactions is described. The salient features for this protocol are the use of an inexpensive and easy-tohandle alkyne source, noble-metal-free condition, wide substrate scope and functional tolerance, satisfactory yield, and simple workup procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Fortunately, the recent research reported that calcium carbide could directly use as solid alkyne source instead of gaseous acetylene in important organic synthesis . Our recent work has also focused on calcium carbide as an alkyne source and reported the synthesis of many active heterocycles …”
mentioning
confidence: 99%
“…Fortunately, the recent research reported that calcium carbide could directly use as solid alkyne source instead of gaseous acetylene in important organic synthesis . Our recent work has also focused on calcium carbide as an alkyne source and reported the synthesis of many active heterocycles …”
mentioning
confidence: 99%